Storage damage of cold-stored whole blood in CPDA maintenance fluid during the whole effective storage period - Yingyu He; Yiquan Zhang; Wanbing Liu; Lidong Zhang; Yingkai Xu; Zihan Yuan; Junying Li; Lei Liu; Fangxiong Cheng (Frontiers in Cell and Developmental Biology)
BackgroundMassive hemorrhage is a leading cause of mortality among trauma patients. To date, whole blood (WB) remains the preferred resuscitation fluid on the battlefield and in pre-hospital emergency care. However, components of WB inevitably undergo storage-related damage, and differences in the duration of storage may lead to varying clinical outcomes after transfusion. This study will involve monitoring cold-stored whole blood (CS-WB) to assess variations in the concentration and activity of each component during in vitro storage.Methods20 bags of WB (400 mL each) from healthy donors were stored at (4 ± 2) °C. Aliquots were collected at storage days 0, 7, 14, 21, 28, and 35 for analysis. On each testing day, storage lesion related indicators of red blood cells (RBCs), plasma components, and platelets were respectively detected.ResultsOn the 14th day of CS-WB storage, no significant changes were found in the morphology, quantity, and function of RBCs. The oxygen carrying capacity of RBCs slightly decreased. Moreover, CS-WB was able to maintain good coagulation function, platelets morphology and hemostatic activity. On the 21st day of CS-WB storage, the oxygen carrying capacity and ATP content of RBCs showed a more significant decrease. Platelets showed characteristic ultrastructural damage and progressive decline in hemostatic function. However, thrombelastogram (TEG) results showed CS-WB could still maintain a certain level of coagulation function and thrombotic ability. By the day 28 of storage, coagulation activity decreased alongside elevated hemolysis markers, indicating progressive and remarkable storage lesion development. On the 28th day of storage, the coagulation activity significantly decreased with the increase of hemolysis markers, indicating that storage damage to active components such as RBCs, platelets, and coagulation factors in CS-WB was ongoing and remarkably developing.ConclusionThese findings show that CS-WB maintained within 14 days of storage provides optimal preservation of critical hemostatic properties, including RBCs oxygen-carrying capacity, coagulation factors function, and platelets hemostatic performance. This storage window holds particular clinical relevance for hemorrhagic shock resuscitation in resource-constrained scenarios, such as military medicine or prehospital trauma care systems.